2012
DOI: 10.1080/07055900.2012.712914
|View full text |Cite
|
Sign up to set email alerts
|

Currents in Luzon Strait Obtained from CTD and Argo Observations and a Diagnostic Model in October 2008

Abstract: On the basis of Acoustic Doppler Current Profiler (ADCP) measurements of current and hydrographic data obtained in October 2008, a diagnostic model of ocean circulation with a modified inverse method is used to study the circulation in Luzon Strait. Satellite-based geostrophic velocity calculated from the merged absolute dynamic topography is also used and compared with the in situ data. The analyses reveal that during the period of observations there were two branches of the Kuroshio current, and the maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…At 121°E, the longitudinal range of high-salinity waters is 20.5-21.7°N. Model results and Argo trajectories also confirm that the intrusion is northwestward (Yuan et al, 2012a).…”
Section: Normal Periodssupporting
confidence: 71%
See 2 more Smart Citations
“…At 121°E, the longitudinal range of high-salinity waters is 20.5-21.7°N. Model results and Argo trajectories also confirm that the intrusion is northwestward (Yuan et al, 2012a).…”
Section: Normal Periodssupporting
confidence: 71%
“…This suggests that, if the front were a wall, it would tilt towards the west. As is known, there is a net flow of upper waters of the WPS into the SCS, while there is a net outflow of intermediate from the SCS (Chen and Huang, 1996;Qu, 2002;Yuan et al, 2012aYuan et al, , 2012b. Why waters with a salinity of 34.15 are not encountered even as far east as 124°E in spring is unknown.…”
Section: Normal Periodsmentioning
confidence: 95%
See 1 more Smart Citation
“…A current mooring system was deployed at M site (Figure ) from March to April 2002, and both observed and modeled currents showed that the Kuroshio intrusion flowed into the SCS through the central LS [ Yuan et al ., ]. Based on the observed results from the Long Ranger 75 K and 150 K, ADCPs deployed at two mooring stations, M2 and M1 (see Figure ) from 25 April to 8 October 2008, the observed subtidal currents and the modeled currents both indicated that (1) a part of the Kuroshio intrusion flows northwestward through the upper layer at section 120°36′E between 20°20′N and 21°20′N in the LS during the spring 2008 [ Yuan et al ., ]; (2) the western branch of Kuroshio flows northwestward (or northward) through the upper layer at section 120°40′E between 20°20′N and 21°00′N in the LS during October 2008 [ Yuan et al ., ]. Based on these findings, the mooring station N2 site (Figure ) is scientifically chosen in the present study to investigate the Kuroshio intrusion.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed seasonal dynamics of the Kuroshio intrusion were recently described using a three‐dimensional diagnostic model with modified inverse methods (MIM) [ Yuan et al ., , ; Liao et al ., ]. Numerical results from these investigations indicated that the northward Kuroshio current east of the LS extends downward to about 700 m, and a westward intrusion from the Kuroshio occurs above depths of 400 m in the LS [ Yuan et al ., , ; Liao et al ., ; Wang et al ., ].…”
Section: Introductionmentioning
confidence: 99%